Cement Stabilization of soft soil subgrade and Cost Analysis - Paneru, Harish; Acharya, Mohan Prasad; Acharya, Indra Prasad (Kathford Journal of Engineering and Management, 2023)
The soft soil when present in subgrade creates a lot of problem in highways. Due to soft soil subgrade, the rutting is predominant cause of flexible pavement failure all around the world. This kind of soil is either replaced or modified prior to construction of other layers of road to minimize the formation of rut. This study deals with stabilization of soft soil subgrade by cement. The sample was collected from a depth around existing road subgrade. A series of laboratory tests on untreated soil sample was first done to determine the competency of soil as a subgrade layer followed by preparation of sample with varying stabilizer content i.e. 4%, 6% and 8% cement by weight of dry soil, to determine the optimum stabilizer content. Samples with varying cement content were also prepared for California Bearing Ratio (hereafter, CBR) and Unconfined Compressive Strength (hereafter, UCS)with different curing periods i.e. 7 days for CBR and 3, 7, 14 and 28 days for UCS. UCS test on these sample showed a significant improvement over the values of natural soil without stabilizer. CBR showed a similar trend and the resulting modified soil was competent enough to be used as a subgrade for heavy traffic condition. The pavement was modelled using Kenpave for 30 and 50 million standard axle (msa) traffic intensity to determine the ideal pavement section for two types of pavement used in this study. In addition, the cost of construction for replacement method and for cement stabilization are determined using norms of Department of Road and District rate of Kathmandu and are compared. The cement stabilized soil with optimum content is found to be cheaper than conventional method of replacement.